Innovation of Cloud-Based Accounting Technology to Improve Business Efficiency and Control - Mostafa Khaled (PT. BATARI EDU CALYA, 2024)
The rapid advancement of digital transformation has compelled businesses across emerging economies to adopt innovative technological solutions for enhanced operational efficiency and financial control. This study investigates the innovation of cloud-based accounting technology and its impact on business efficiency and control within the Egyptian business context. Employing a quantitative research methodology utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), this research examines the relationships between cloud accounting adoption, operational efficiency, financial reporting quality, and organizational control mechanisms. Data were collected from 285 Egyptian enterprises that have implemented cloud-based accounting systems. The findings reveal that cloud-based accounting technology significantly enhances business efficiency through real-time data accessibility, automated accounting processes, and improved data security protocols. Furthermore, the results demonstrate that organizational and human factors play critical roles in successful cloud accounting adoption, while technological infrastructure and perceived trust serve as moderating variables. The study contributes to the existing literature by providing empirical evidence from the Egyptian context, offering practical implications for businesses seeking to leverage cloud technology for competitive advantage. The research concludes that strategic implementation of cloud-based accounting systems, coupled with adequate organizational readiness and human capital development, can substantially improve business efficiency and control mechanisms in emerging market economies.